\[\boxed{\text{868\ (868).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[y = x - 1\]
\[x\] | \[0\] | \[1\] |
---|---|---|
\[y\] | \[- 1\] | \[0\] |
\[y = \frac{1}{4}x + 2\]
\[x\] | \[0\] | \[4\] |
---|---|---|
\[y\] | \[2\] | \[3\] |
\[Ответ:(4;3).\]
\[\boxed{\text{868.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[\textbf{а)}\ \left( \text{ab} + 1 \right)^{2} - (a + b)^{2} =\]
\[= (\text{ab} + 1 - a - b)(\text{ab} + 1 + a + b)\]
\[\textbf{б)}\ \left( \text{ab} + 1 \right)^{2} - (a + b)^{2} =\]
\[a^{2}b^{2} + 2ab + 1 - a^{2} - 2ab - b^{2} =\]
\[= a^{2}b^{2} - a^{2} + 1 - b^{2} =\]
\[= a^{2}\left( b^{2} - 1 \right) - \left( b^{2} - 1 \right) =\]
\[= \left( b^{2} - 1 \right)\left( a^{2} - 1 \right) =\]
\[= (b - 1)(b + 1)(a - 1)(a + 1)\]
\[\textbf{а)}\ (a + 2b)^{2} - (ab + 2)^{2} =\]
\[= (a + 2b - ab - 2)(a + 2b + ab + 2)\]
\[\textbf{б)}\ (a + 2b)^{2} - (ab + 2)^{2} =\]
\[= (1 - b)(1 + b)(a - 2)(a + 2)\]